Selection of New Potential Genotype from Exotic Wheat Germplasm Based on Agronomic Traits and Biochemical Analysis - Matiur Rahman; Ejaz, Sania; Khan, Wasim; Begum, Syeda Sundas; Zia, Ziaulhaq; Islam, Badshah; Rasheed, Shayan; Gul, Safia; Ali, Mansoor (Indus Journal of Bioscience Research, 2025)
This study aimed to evaluate the genetic diversity and identify high-yielding wheat (Triticum aestivum) genotypes through both morphological and biochemical analyses. A total of 36 wheat genotypes, including three local cultivars and thirty-three exotic genotypes, were analyzed for 16 morphological traits and protein profiles using SDS-PAGE. The genotypes exhibited considerable variability, with the cluster analysis of morphological traits revealing four major clusters, reflecting distinct genetic backgrounds. Significant correlations were observed between several morphological traits, such as stem length, spike length, and total plant height, all of which were closely associated with grain yield. Genotypes like Ma-6, Ma-16, Ma-22, and Ma-30 demonstrated superior performance, with increased spikelet numbers and 1000-seed weight, indicating their potential for high-yielding wheat breeding. The molecular analysis revealed 10 protein bands, 2 of which were monomorphic, and 8 were polymorphic, reflecting high genetic diversity. Four distinct clusters were identified based on protein profiles, confirming the genetic differentiation observed in the morphological data. Specific loci such as L-5 and L-6 exhibited significant variation, which may be linked to traits like disease resistance or drought tolerance. The results highlight the importance of using a multi-trait approach, combining both phenotypic and molecular data, for more accurate assessments of genetic diversity. This study identifies promising genotypes for future wheat breeding programs focused on improving yield, grain quality, and adaptability to diverse environmental conditions. The findings emphasize the value of integrating both morphological and molecular data in wheat breeding efforts to address challenges posed by climate change and other environmental stresses.